Rethinking diversity frameworks in higher education - Chun, Edna Breinig; Feagin, Joe R. (New critical viewpoints on society series., 2020)
"The book offers concrete approaches, concepts, and tools that will enable higher education leaders to identify, address, and counteract persistent structural and behavioral barriers to inclusion. As such, it shares a series of practical recommendations that will assist presidents, provosts, executive officers, boards of trustees, faculty, administrators, diversity officers, human resource leaders, diversity taskforces, and researchers as they seek to implement comprehensive strategies that result in sustained diversity change"--